Transgenerational effects of the genocide against the Tutsi in Rwanda: A post-traumatic stress disorder symptom domain analysis [version 2; peer review: 2 approved, 1 approved with reservations] - Monica Uddin; Susan Rudahindwa; Leon Mutesa; Jean Mutabaruka; Eugene Rutembesa; Derek E. Wildman; Annie Qu; Stefan Jansen (Open Research Africa)
Background: A number of studies have investigated transgenerational effects of parental post-traumatic stress disorder (PTSD) and its repercussions for offspring. Few studies however, have looked at this issue in the African context. Methods: The present study addresses this gap by utilizing a Pearson correlation matrix to investigate symptom severity within the three Diagnostic and Statistical Manual of Mental Disorders IV (DSM-IV) PTSD symptom domains in mothers exposed to the genocide against the Tutsi in Rwanda (n=25) and offspring (n=25), and an ethnically matched set of controls (n=50) who were outside of Rwanda during the 1994 genocide. All mothers were pregnant with the offspring included in the study during the time of the genocide. Results: Total PTS score was significantly (p<0.01) correlated with each of the three symptom domains at various strengths in both cases and controls. No significant differences in association of total PTS score and PTSD symptom domains were observed between exposed mothers and offspring, suggesting that each symptom domain contributed equivalently to both exposed mothers and offspring distress. In contrast, the re-experiencing symptom domain showed a significant difference in correlation to overall PTS score in non-exposed mothers compared to their offspring (p<0.05), with mothers showing a significantly higher correlation. Furthermore, the correlation between avoidance/numbing symptoms to overall PTS was significantly different (p≤0.01) across exposed and non-exposed mothers. As a secondary analysis, we explored the relationship between DNA methylation in the glucocorticoid receptor (NR3C1) locus, an important stress modulating gene, and PTSD symptom domains, finding an association between DNA methylation and re-experiencing among genocide-exposed mothers that exceeded any other observed associations by approximately two-fold.  Conclusions: This is the first report, to our knowledge, of a symptom-based analysis of transgenerational transmission of PTSD in sub-Saharan Africa. These findings can be leveraged to inform further mechanistic and treatment research for PTSD.